Morocco : Financial Sector Strategy Note - World Bank (Washington, DC, 2013)
The report presents an overview of financial sector reforms in Morocco, between 1990-1998, a period notable for liberalization. Reforms targeted the banking sector, development of the capital market, and liberalization of the financial sector, with recent reform efforts focused on savings institutions (insurance and pension funds). Included were the elimination of credit ceilings, interest rate liberalization, and overhaul of the legislative framework governing lending institutions, namely through the adoption of the new Banking Law of 1993. As a result, the financial sector is increasingly operating in accordance with market rules, and, financial inter-mediation has intensified. The financial situation of commercial banks is healthy, and has clearly improved since 1993, with foreign exchange risk exposure well below prudential limits. However, management of credit risk should improve, due to the high percentage of non-recoverable loans. Return on equity of Moroccan banks has been satisfactorily achieved, despite weak responsiveness by bank lending, and short-term rates to market conditions. Recommendations include reduction of bank inter-mediation costs, while preserving financial soundness; improvement of bank prudential regulation, and financial disclosure; increased lending and savings competition; and, promotion of market-based interest rates, and, reform of the government securities market.